Utterance of David, the Anointed of the God of Jacob (2 Samuel 23:1-7) - Leonard-Fleckman, Mahri (Journal of Biblical literature, 2018)
Building on earlier studies of 2 Sam 23:1-7, I explore unique features of the poem that set it apart from the conceptual framework of Samuel-Kings and reflect a later development in the Davidic traditions. My primary foci are the concept of David the prophet (vv. 1-2) and the link between David and the God of Jacob (vv. 1 and 3), as well as the description of the just and perhaps unidentified ruler (vv. 3-7) and the panorama of divine names throughout. The poem represents the earliest witness to the development of David's prophetic image in early Judaism and Christianity. Yet the poetry does not merely demonstrate independence and innovation; rather, it draws deeply from earlier traditions, including the Balaam material and imagery from the Prophets and the Psalms. This analysis furthers earlier proposals that, before its inclusion in the appendix of 2 Samuel, the likely context for "David's last words" was the Psalms.